Model of land acquisition productivity performance for toll road projects in Indonesia - Putri, Kartika Nur Rahma; Marzuki, Puti Farida (Fakultas Teknik UB, 2020)
Land acquisition process in the Indonesian toll road project has a high level of uncertainty. Several previous studies mainly discuss the risks involved in toll road projects and their mitigation measures, but the effect of existing risks on land acquisition scheduling is rarely reviewed. This research aims to develop a model for land acquisition productivity performance for toll road projects. The performance of productivity was modelled based on a predefined duration mentioned in Indonesian Act. No. 2/2012, compared to the actual duration from 6 toll road projects using montecarlo simulation. The validity of model was tested using the Section II of Cisumdawu Toll Road project. The simulation productivity result was 23.13 km/year, with a standard deviation of 6.704 km/year. Meanwhile, the actual productivity was 20.50 km/year, which was still within the range of the simulation's standard deviation. Hence, the models could reasonably describe the reality of the project. The most important activities that could affect land acquisition productivity performance were payment of compensation, the determination of compensation value, settlement of claims for the forms of compensation, and the identification and inventory of land ownership data.